Digital Narratives and Tradition: The Role of NU Kids Animations in Early Islamic Education - Rashid Said Al Mushaiqri, Mahfouda; Sulistio, Dody (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to analyze the impact of animated content on the NU Kids YouTube channel on traditional Islamic education for early childhood by examining viewership metrics, community engagement, behavioral changes in children, and how these animations integrate character education, appreciation for local traditions, and the formation of a moderate religious identity. Design/methods/approach – A netnographic approach was employed to observe and analyze 7 out of 13 available videos on the NU Kids Sumenep channel. These 7 videos were selected based on their thematic relevance to the research objectives, focusing on the portrayal of Nahdlatul Ulama’s history, character education, and the development of religious identity. Thematic analysis was used to identify key themes in these videos, including representations of Nahdlatul Ulama history, character education, and the development of religious identity. Findings – The findings indicate that NU Kids animations successfully promote traditional Islamic values rooted in local traditions. For instance, episodes such as